Total quality management practices among halal certified food SMEs in selected states of Malaysia - Abu Karim, Rizuwan (2017)
Considering the incidences of Shariah compliance of halal food products sold in the market, this study examines does TQM practices can influence food product with halal certification and what is the impact of food product with halal certification towards the performance of SMEs food manufacturers. Specifically, the study examines the relationship between strategic planning, information management, top management, process management, human resource and customer focus as variables that can influence trust and safety attributes of food product with halal certification. This research also investigates the impact of trust and safety towards the organizational performance of SMEs food manufacturer. Drawing upon the integration between TQM practices and product quality as well as the impact of food safety system and organizational performance, a conceptual framework in this study is developed. A quantitative approach is employed to achieve the objective of the study. Data were collected from 200 SMEs food manufacturers via survey questionnaire developed from related literature and discussion held with practitioners. The data collected were then analysed using structural equation modelling via WarpPLS 4.0. The findings of this study indicated that strategic planning had significant positive relationship with trust and safety. Information management also found had significant positive relationship with trust and safety. Findings also demonstrated that there is a significant positive relationship between top management and trust as well as safety. Moreover, findings indicated that process management only had positive significant relationship with trust. In addition, findings also shown that human resource only had positive significant relationship with safety. As for the impact of trust and safety towards performance of the certified halal SMEs food manufacturers, this study found that trust and safety have a significant impact on organizational performance. Examining the elements that can be used by food manufacturers in Malaysia, findings of this study explains how the halal food production process can be improved. The conceptual framework also serves as a foundation to improve the performance of food manufacturers.